Subjectless Complement Sentences In Universal Grammar - ABDELMOUMENE-HOCINE, N (Journal of Human Sciences, 2001)
Our purpose in the present article is to provide an adequate description of one feature type of sentential complements: subjectless complement clauses, by looking at the grammar of a range of languages. Obviously, languages do differ as for the internal and external structures of their complement sentences. Our aim in this description is to analyse subjectless complements cross-linguistically in order to find out some common features among the languages under study or some features specific to a certain number of languages. The procedure we will be following is that starting from the structure or type of variation we are looking for, we’ll end up with the language or the illustration in order to see how each language is different or similar to other languages and if it is so, we’ll try to find out what different or similar features it has.